Etika Komunikasi Netizen Indonesia Di Media Sosial Sebagai Ruang Demokrasi dalam Telaah Ruang Publik Jurgen Habermas - Stepanus Angga; Antonius Alfredo Poa; Fabianus Rikardus (Jurnal Filsafat Indonesia, 2023)
The focus of this writing is to question the phenomenon of netizen comments on various social media accounts as a space for freedom of expression. Social media often allows many people to express their feelings and circumstances. At the same time, social media has become a public space for conveying ideas to many people. In it, people are free to have opinions and comments without having strong validity. These netizen comments apparently can lead people to irrational communication because they are done without consideration. So in the methodology of writing this article, the researcher conducted a qualitative research study by searching for data through journals and books related to the communication ethics of Indonesian netizens. This paper will be based on the philosophy of public space by Jurgen Habermas who makes several claims in communicating. Then, after the data was collected, the researcher used the content analysis method to examine the research data. The analysis will produce research findings, namely that the communications and opinions conveyed in the comments column are often without rational consideration. Netizens tend to get carried away to participate in comments without understanding reality well. Social media is only seen as an ordinary public space without any element of rationality that respects each other's rights and encourages the formation of social solidarity.